Καταγραφή μερικών υγρότοπων στις επαρχίες Λάρνακας – Αμμοχώστου και εισήγηση σειράς μέτρων για αειφόρο διαχείρισή τους - Μάντζιπας, Ραφαήλ (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This study dealt with the recording and collection of data for a number of wetlands located in the region of Larnaca and free Famagusta in Cyprus, with a view to evaluating the current situation. Furthermore it suggests important measures for the improvement and maintenance of the environment, the society and the economy. The study was based in Salt Lakes (aliki) and the lake in Larnaca Voroklini as part of Larnaca area, while in Famagusta was studied Achna Dam, Lake Paralimni, the sewage tanks of Ayia Napa, Liopetri River, the dam Aftellotos in Ayia Napa and tanks livestock waste water in forest area of Dasaki of Achnas. The data which is analyzed for each region separately are referring to the general position of the wetland area and the current situation in the region. Moreover, data of flora, fauna and habitat types is recorded in each region separately. At the same time, the study is referring to protected status of areas, as well as ecological functions representing each region. In addition, the study refers to Akamas history of each wetland and the significant and the numerous ways of use from human being. Finally the study refers to threats of each wetland that may alter or degrade the naturalness and any ecological functions offered in the region. In general, the work performed discusses the situation of wetland regarding maintenance and rescuing varies moderately. People`s multiple use, increases the risk to retain and rescue of the area. The waste discharges, poaching, constant construction development, the undeveloped grazing and use of pesticides in agriculture, increased road network and lack of environmental education leading these regions to disaster. As a result, a policy is considered necessary for their sustainable development. This policy must have as its main objectives the preservation and enhancement of habitat types and flora and fauna. In addition, it should be included the maintaining and improvement of the water and soil quality, along with the prevention of harmful activities for wetlands. All of the above can be accomplished by a combination between the promotion of the environmental education and the harmonious coexistence of wetlands to humans. In this context, it was suggested a series of measures - measures for sustainable management of wetlands.
Keywords: Wetlands; Larnaca; Famagusta; Salt lakes; Sustainable development; Υγρότοποι; Λάρνακας; Αλυκές; Αμμόχωστος; Αειφόρος ανάπτυξη